Primitive compact flat manifolds with holonomy group Z2 ⊕ Z2 - Tirao, Paulo Andres (2001)
In this paper we determine and classify all compact Riemannian flat manifolds with holonomy group isomorphic to Z2 ⊕ Z2 and first Betti number zero. Also we give explicit realizations of all of them.